The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/ases.12208
|View full text |Cite
|
Sign up to set email alerts
|

Major venous resection and reconstruction using a minimally invasive approach during laparoscopic pancreaticoduodenectomy: One step forward

Abstract: In the current era of technological advancement, the feasibility of laparoscopic pancreaticoduodenectomy has been established. However, major venous resection and reconstruction along with laparoscopic pancreaticoduodenectomy is still considered a complex procedure. A 47-year-old woman presented with obstructive jaundice secondary to carcinoma in the pancreatic head. Triphasic abdominal CT revealed a 2.7 × 3.0-cm heterogenous mass in the pancreatic head with peripancreatic lymphadenopathy without vascular invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…As early as 2011, Kendrick and colleagues reported the initial experience of major venous resection during total laparoscopic pancreatoduodenectomy, which first demonstrated the feasibility of this technique. [26] Later on, Panalivelu [13] reported a case that underwent laparoscopic end-to-end anastomosis, and Dokmak [14] reported a case that underwent laparoscopic partial venous excision using a patch, respectively. Recently, Khatkov demonstrated the feasibility and safety of laparoscopic pancreatoduodenectomy with venous reconstruction in eight patients.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2011, Kendrick and colleagues reported the initial experience of major venous resection during total laparoscopic pancreatoduodenectomy, which first demonstrated the feasibility of this technique. [26] Later on, Panalivelu [13] reported a case that underwent laparoscopic end-to-end anastomosis, and Dokmak [14] reported a case that underwent laparoscopic partial venous excision using a patch, respectively. Recently, Khatkov demonstrated the feasibility and safety of laparoscopic pancreatoduodenectomy with venous reconstruction in eight patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies from multiple centers have shown that, compared with PD, the incidences of intraoperative bleeding, postoperative incision-related complications, and hospital stay in LPD are lower, while the incidences of severe complications, such as hemorrhage and pancreatic fistula, are not significantly higher. The value of LPD in practical application has been confirmed[14-16]. For patients with tumor invasion of the portal vein/SMV, the range of LPD resection and dissection can reach the standard PD level[16-18].…”
Section: Discussionmentioning
confidence: 99%
“…The value of LPD in practical application has been confirmed[14-16]. For patients with tumor invasion of the portal vein/SMV, the range of LPD resection and dissection can reach the standard PD level[16-18]. The incidence of postoperative complications and mortality are not significantly increased, giving LPD a certain advantage over PD[19].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have reported the technical and oncological feasibility of LPD combined with venous vascular resection 11121314151617. In the current report, we present the case of a patient with pancreatic head cancer who underwent successful LPD with segmental resection of the SMV–SV–PV confluence, resulting in negative surgical margins.…”
Section: Introductionmentioning
confidence: 92%